Digital Micro-Learning (DML) Based e- Training for Enhancing Digital Competence of Teacher Educators - Khalil, Aysha; Sultana, Naveed (International Journal of Psychosocial Rehabilitation, 2020)
E-Training has gained potential enticement in this era of digitized educational networks. Countries like Pakistan have smaller trends of e-Training programs as teachers are not digitally competent enough. They take such programs as professional burden, wastage of time and cognitive load Digital Micro-Learning (DML) addresses these issues of as DML is a strategy of training through brief, digestible, and well-planned units of information which are consumed by the trainees via digital media. DML contains micro-content and micro- activities within digital training environment. For this research study, e-Training program was conducted on the concept of Digital Micro-Learning which was intended to enhance the digital competence of teacher educators focusing on enhancement of digital literacy and e-Teaching skills. Findings of the study revealed the higher engagement level during e-Training and enhanced digital literacy and e-Teaching skills. The study suggests using DML approach for continued professional development of teacher educators.